ENHANCING EFL STUDENTS’ RECOUNT TEXTS BY EMPLOYING METACOGNITIVE LEARNING STRATEGIES (MLS) - Dhillon, Bobby Pramjith Singh; Musthafa, Bachrudin; Wirza, Yanti (University of Kuningan, 2024)
Although writing in English is challenging for non-native students, metacognitive learning strategies could be the solution. Therefore, this paper aims to examine and describe if students' metacognitive learning strategies and writing abilities are positively and significantly correlated during the second semester at Nommensen University in Pematangiantar, Indonesia. The text was analyzed using a correlation study with 25 writing II students. In this study, two different kinds of variables were used. The first is the independent variable—the students' metacognitive learning strategies—and the second is the dependent variable—their writing skills. Pearson's simple product-moment correlation was employed to evaluate the collected data. A questionnaire modified from the theory of metacognitive learning strategies was used to assess the students’ metacognitive learning strategies. A written test using recount texts assesses students' English writing ability. The researchers conducted interviews to see how students who used metacognitive learning strategies responded to writing and interviewed English teachers to confirm the findings. The result showed a significant correlation between the students' metacognitive learning strategies and the students' writing skills (r = 0.590 > r table = 0.505). Therefore, the teacher and students need to consider metacognitive learning strategies in the learning process to develop their writing skills.